2019
DOI: 10.1108/jic-05-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

Protecting intellectual property from insider threats

Abstract: Purpose The purpose of this paper is to propose a theory of information security intelligence and examine the effects of managers’ information security intelligence (MISI) on employees’ procedural countermeasure awareness and information security policy (ISP) compliance intention. Design/methodology/approach A survey approach and structural equation modeling is utilized. Partial least squares (WarpPLS 6.0) and nonlinear algorithm are employed to analyze and examine the hypotheses. In total, 324 employees fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…In order to boost employees' information security compliance intention behavior, Kim, Hovav and Han (2020) also recommended that the company's security executives exhibit information security expertise and problem-solving skills. Other studies have shown that the information security leader is crucial to supporting information security initiatives and ensuring the success of the organization's information security awareness programs (Hong and Furnell, 2021;Ameen et al, 2021).…”
Section: Information Security Intelligence (Isi) Competencies and Cyb...mentioning
confidence: 99%
“…In order to boost employees' information security compliance intention behavior, Kim, Hovav and Han (2020) also recommended that the company's security executives exhibit information security expertise and problem-solving skills. Other studies have shown that the information security leader is crucial to supporting information security initiatives and ensuring the success of the organization's information security awareness programs (Hong and Furnell, 2021;Ameen et al, 2021).…”
Section: Information Security Intelligence (Isi) Competencies and Cyb...mentioning
confidence: 99%
“…Thus, ICCS should be an integral part of the management of IC. The value of IC is directly linked to an organization's ability to manage its IC in an efficient (Secundo et al , 2017) and secure way, including protecting intellectual property from insiders (Kim et al , 2019). Because IC is composed of human capital (HC), structural capital (SC) and relational capital (RC; Bontis, 1998; Choong, 2008), ICCS is challenged by threats on each of these three levels (Renaud et al , 2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Although in recent years, there has been emerging interest in the internal behavioral risk of ICCS (Bongiovanni et al , 2020; Kim et al , 2019), a dearth of research remains in this domain for several reasons including the infancy of ICCS field and by implication a lack of nascent security theories within the IC literature. One way to fill this need is to draw upon a non-identical yet similar field of research that has mature security literature and adopt constructs and models to explain and advance relevant ICCS theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Educate employees about intellectual property. Employees should be made aware of the value, boundaries, and risk of IP (or lack thereof) [83][84][85]. Training should make clear to them what needs to be protected, how to protect it, and from whom it should be protected [83][84][85].…”
mentioning
confidence: 99%